Aplikasi Monitoring Pola Makan Untuk Anak Overweight Dan Underweight - Denny Nur Jayanto; Nia Saurina; Firman Hadi Sukma Wijaya (Melek IT : Information Technology Journal, 2017)
The nutritional adequacy of the numbers is a value used to determine the number of substances that are either consumed by the body and what are the substances needed by our body. This required a science that has been used to know clearly how the nutritional calculation procedures. On this research, Application Monitoring Eating Patterns For Children Overweight and Underweight aiming to help the parents of children in order to monitor the child's diet. This research uses the method Waterfall which includes Requirement Planning, perform data collection in need of data collection, the literature study books, and journals and do an interview with a nutritionist. This system design using UML (unified modeling language) with the creation of Android-based applications. With the aim of informing information RDA for children Overweight and Underweight to any parents who have children who are still aged 7 to 12 years and help monitor the food so that the children obtain information appropriate food RDA. The results of this research are the application of RDA has been able to do calculations in accordance with the dietary needs of the child, this can be proved on application monitoring eating patterns for childhood overweight and underweight. Moreover, the application can help parents monitor children’s meals that have a weight is not ideal.